Topological Kondo insulators in one dimension: Continuous Haldane-type ground-state evolution from the strongly interacting to the noninteracting limit - Lisandrini, Franco Thomas (2017)
We study, by means of the density-matrix renormalization group (DMRG) technique, the evolution of the ground state in a one-dimensional topological insulator, from the noninteracting to the strongly interacting limit, where the system can be mapped onto a topological Kondo-insulator model. We focus on a toy model Hamiltonian (i.e., the interacting "sp-ladder" model), which could be experimentally realized in optical lattices with higher orbitals loaded with ultracold fermionic atoms. Our goal is to shed light on the emergence of the strongly interacting ground state and its topological classification as the Hubbard U interaction parameter of the model is increased. Our numerical results show that the ground state can be generically classified as a symmetry-protected topological phase of the Haldane type, even in the noninteracting case U=0 where the system can be additionally classified as a time-reversal Z2-topological insulator, and evolves adiabatically between the noninteracting and strongly interacting limits.